The Pentadic Universe in the Sanskrit Text of Saivagamas - Balakailasanathasarma, M. (University of Kelaniya, 2017)
In the integral vision of the Saivagamas the world is seen to be composed of consciousness (cinmaya), flooded with light, made of light and permeated with light (prakasa), but though being consciousness in essence a substance is seen and experienced as insentient. The question baffles us why being consciousness in essence it is perceived as insentient. To this question the answer given by the Saivagamas is that the substance is apparently seen to be insentient in so far as it dose not have self-reflection of its own. Only because of the absence of self-reflection some substances are considered insentient and are therefore relegated to the level of matter but some others on account of self-reflection, are raised to the highest excellence of spirit, the sentient beings. In Saivagamas speciallyin the non-dualistic Saivagamas, no such dichotomy of spirit and matter exists, rather it sees it as an integrated whole. The Saivagamas also do not like to classify the whole into asti, bhati, priya, nama and rupa like the Vedantins stigmatizing the world of the name and form to be negated, conceiving it to be illusory while accepting only that aspect of Brahman which is being, consciousness and bliss. But the ideal vision of the Saivagamas is to see everything as the One, not many. It explains Saivagamas of the Upanisadas the entirety, not multiplicity (nana) because in this integral vision there is no such diversity that is not in essence light (prakasaparamartha). The universe as it shines before us consists of two aspects- the one is signifier called vacaka and the other is paramarsa, the process of cognition manifesting itself in the vacya, the signified consciousness. In the Agamas the accepted number of principles is thirty-six but even there the scheme of grouping them into five divisions can be possible. So the Agamic thinkers not only see the ptesence of five categories in the gross level of their manifestation but also on the subtle level. To conclude we may say that the bhutas (elements) are thought to be the basic elements of the world-the world of pain and pleasure. But to the agamic thinkers they should be utilized in a different way in order to attain the ultimate goal of life. We have discussed that the bhutas have gross, subtle and the highest forms. To the aspirant the base from which he starts his sadhana and tries to see the dynamic form of it everywhere in order to achieve his aim of Sivahood.
Keywords: Consciousness; Insentient; Universe; Reflection; Saivagamas